A Narrative Review of Circular RNAs in Brain Development and Diseases of Preterm Infants - Gu, Qianying; Liu, Heng; Ma, Jingjing; Yuan, Jiaming; Li, Xinger; Qiao, Lixing (Frontiers in Pediatrics, 2021)
Circular RNAs (circRNAs) generated by back-splicing are the vital class of non-coding RNAs. CircRNAs are highly abundant and stable in eukaryotes, and many of them are evolutionarily conserved. They are blessed with higher expression in mammalian brains and could take part in the regulation of physiological and pathophysiological processes. In addition, premature birth is important in neurodevelopmental diseases. Brain damage in preterm infants may represent the main cause of long-term neurodevelopmental disorders in surviving babies. Until recently, more and more researches have been evidenced that circRNAs are involved in the pathogenesis of encephalopathy of premature. We aim at explaining neuroinflammation promoting the brain damage. In this review, we summarize the current findings of circRNAs properties, expression and functions, as well as their significances in the neurodevelopmental impairments, white matter damage and ischemic-hypoxic encephalopathy. So we think that circRNAs have a direct impact on neurodevelopment and brain injury. Even though their exact roles and mechanisms of gene regulation remain elusive, circRNAs have potential applications as diagnostic biomarkers for brain damage and the target for therapeutic intervention.